Current and future treatment options for MET exon 14 skipping alterations in non-small cell lung cancer. (February 2021) - Hong, Lingzhi; Zhang, Jianjun; Heymach, John V.; Le, Xiuning
It has been over three decades since the hepatocyte growth factor (HGF) ligand and its receptor MET proto-oncogene (MET) pathway was established as promoting cancer growth and metastasis. MET exon 14 skipping ( METex14 ) alterations occur in 3–4% of all non-small cell lung cancer (NSCLC) patients, typically in elderly patients (older than 70 years), and result in constitutive activation of the MET receptor by altering a region required for receptor degradation. Multi-kinase inhibitor of MET, such as crizotinib, and more recently selective MET inhibitors, such as capmatinib and tepotinib, have demonstrated clinical efficacy and safety in METex14 NSCLC patients in clinical trials. These results have led to the approval of MET inhibitors by regulatory agencies across the globe. The success also fueled the excitement of further development of therapeutic strategies to target METex14 in lung cancers. This article provides an overview of the clinical development program targeting METex14 in NSCLC, including small molecular tyrosine kinase inhibitors and anti-MET antibodies. Furthermore, combination therapy immune checkpoint inhibitors or other targeted therapies are also under development in various patient populations, with acquired resistance immune or targeted therapy. Clinical trials in different development stages are ongoing and more drugs targeted to c-MET will be available for NSCLC patients with METex14 skipping mutations in the future.